Allograft Versus Autograft Osteochondral Transplant for Chondral Defects of the Talus: Systematic Review and Meta-analysis. Issue 12 (October 2022) - Migliorini, Filippo; Maffulli, Nicola; Baroncini, Alice; Eschweiler, Jörg; Knobe, Matthias; Tingart, Markus; Schenker, Hanno
Background: It is unclear whether the results of osteochondral transplant using autografts or allografts for talar osteochondral defect are equivalent. Purpose: A systematic review of the literature was conducted to compare allografts and autografts in terms of patient-reported outcome measures (PROMs), MRI findings, and complications. Study Design: Systematic review; Level of evidence, 4. Methods: This study was conducted according to the PRISMA guidelines. The literature search was conducted in February 2021. All studies investigating the outcomes of allograft and/or autograft osteochondral transplant as management for osteochondral defects of the talus were accessed. The outcomes of interest were visual analog scale (VAS) score for pain, American Orthopaedic Foot and Ankle Society (AOFAS) score, and Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score. Data concerning the rates of failure and revision surgery were also collected. Continuous data were analyzed using the mean difference (MD), whereas binary data were evaluated with the odds ratio (OR) effect measure. Results: Data from 40 studies (1174 procedures) with a mean follow-up of 46.5 ± 25 months were retrieved. There was comparability concerning the length of follow-up, male to female ratio, mean age, body mass index, defect size, VAS score, and AOFAS score ( P > .1) between the groups at baseline. At the last follow-up, the MOCART (MD, 10.5; P = .04) and AOFAS (MD, 4.8; P = .04) scores were better in the autograft group. The VAS score was similar between the 2 groups ( P = .4). At the last follow-up, autografts demonstrated lower rate of revision surgery (OR, 7.2; P < .0001) and failure (OR, 5.1; P < .0001). Conclusion: Based on the main findings of the present systematic review, talar osteochondral transplant using allografts was associated with higher rates of failure and revision compared with autografts at midterm follow-up.